The Extracellular Matrix Enriched With Exosomes for the Treatment on Pulmonary Fibrosis in Mice - Yu, Yanzhen; Liu, Xingzhi; Zhao, Zhe; Xu, Zhongjuan; Qiao, Yong; Zhou, Yuanshuai; Qiao, Hong; Zhong, Junjie; Dai, Jianwu; Suo, Guangli (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis (PF) is a severe respiratory disease caused by lung microenvironment changes. TGF-β/Smad3 signaling pathway plays a critical role in the fibrotic process. MicroRNA-29 (miR-29) has proved to alleviate the occurrence of PF by downregulating TGF-β/Smad3 signaling pathway. The miRNA application encounters obstacles due to its low stability in body and no targeting to lesions. Exosomes can be used for therapeutic delivery of miRNA due to their favorable delivery properties. However, low efficiency of separation and production impedes the therapeutic application of exosomes. In this study, we developed a liquid natural extracellular matrix (ECM) enriched with miR-29-loaded exosomes for PF treatment. The collagen‐binding domain (CBD)-fused Lamp2b (CBD‐Lamp2b) and miR-29 were overexpressed in human foreskin fibroblast (HFF) host cells for the entrapment of miR-29-loaded exosomes in ECM of the cells. The repeated freeze-thaw method was performed to prepare the liquid ECM enriched with exosomes without destroying the exosomal membrane. In summary, this study developed a novel functional ECM biomaterial for therapy of PF, and also provided a promising gene therapy platform for different diseases by treatment with liquid ECM that is enriched with exosomes loaded with different functional miRNAs.